The great frozen sea : a personal narrative of the voyage of the "Alert" during the Arctic epedition of 1875-6 - Markham, Albert Hastings, Sir, 1841-1918. (London : C.K. Paul, 1880)
Published also in French under title: La mer glacée du pôle (see CIHM microfiche no. 04665) Reproduction of original in: Public Archives of Canada. Includes index. Mode of access: Internet.